Recent years have seen massive advances in communication technology. The continuously incrementing demands of high bandwidth, data rates and spectrum efficiencies have fostered the exploitation of terahertz (THz) and sub-terahertz (S-THz) communications, - et. al., Dr.Ananth Kumar M.S, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Recent years have seen massive advances in communication technology. The continuously incrementing demands of high bandwidth, data rates and spectrum efficiencies have fostered the exploitation of terahertz (THz) and sub-terahertz (S-THz) communications, opening broad opportunities in the development of THz and S-THz antennas. This paper presents a brief review of antennas in THz and S-THz frequency bands. It describes the scope of THz spectrum in wireless communication and explains the unique radiation characteristics of the THz spectrum. The paper also enumerates the crucial benefits of implementing THz band in communication systems. Furthermore, this work reviews several antenna designs and their performances and even explores antennas of different shapes employed in numerous studies for THz and S-THz applications. This article gives a brief comparative survey of various shaped antenna designs for THz/S-THz band operations and analyzes the key findings of reviewed works and investigates the further developments needed in antenna designs, their structures and performance parameters for introducing, developing and optimizing antennas appropriate for diverse THz/S-THz applications.